Comparison of Long-term Changes in Pain and Depression after Major Elective Surgeries Among Seriously Ill Older Adults - Ahmad, Wasim; Iqbal, Sikandar; Qayyum, Saqib; Shehzad, Khurram; Saifullah; Nazir, Muhammad Tariq; Usman, Tariq; Faraz, Ahmad (Indus Journal of Bioscience Research, 2025)
Background: Major elective surgeries are critical interventions that can significantly influence the trajectory of health and quality of life for seriously ill older adults. Objective: To evaluate the long-term changes in pain, depression, functional status, and informal caregiving burden in older adults undergoing major elective surgeries. Methods: This retrospective observational was conducted at Gomal Medical College, Dera Ismail Khan, Pakistan, from 1st September 2023 to 31st August 2024. Data were collected from 150 patients aged > 55 years. Baseline assessments are conducted before surgery to establish initial measures of pain, depression, functional status, and caregiving burden. Patients and caregivers participate in structured interviews and complete validated questionnaires during these assessments. Results: Pain severity decreased significantly from a baseline mean of 6.2 (±1.5) to 3.1 (±1.4) at 12 months, though 20% of patients reported persistent moderate to severe pain. Depression initially worsened but improved by 12 months, with only 15% of patients exhibiting symptoms. Functional independence improved in 80% of patients by 12 months, exceeding baseline levels in 25%. Caregiving burden peaked at 1 month and declined gradually but remained slightly elevated in 20% of cases at 12 months. Higher baseline pain and depression scores were associated with poorer outcomes. Conclusion: Major elective surgeries result in significant improvements in pain, depression, and functional status, but persistent challenges necessitate targeted interventions. Supporting both patients and caregivers is crucial to optimizing long-term outcomes.